2014
DOI: 10.1684/ejd.2013.2241
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency is associated with higher carotid intima-media thickness in psoriatic patients

Abstract: Vitamin D insufficiency is associated with higher carotid intima-media thickness in psoriatic patientsBackground: Psoriasis has been associated with vitamin D insufficiency and cardiovascular risk factors. Reports show that serum 25-hydroxyvitamin D (25-OHD) levels are inversely associated with chronic inflammatory systemic diseases, cardiovascular risk factors and cardiovascular outcomes. Objective: To analyze the association between 25-hydroxyvitamin D serum levels and subclinical carotid atherosclerosis (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…After full manuscripts assessed for eligibility, 26 articles appeared to satisfy the inclusion criteria. Six articles were excluded for the following reasons: one study 35 did not provide SD of the outcome; 2 studies 36 , 37 did not provide average intima-media thickness values; and participants’ selection did not match with age or sex in 2 studies. 38 , 39 One study 40 was further excluded because the reported FMD value was particularly high in both psoriatic patients and controls than other studies.…”
Section: Resultsmentioning
confidence: 99%
“…After full manuscripts assessed for eligibility, 26 articles appeared to satisfy the inclusion criteria. Six articles were excluded for the following reasons: one study 35 did not provide SD of the outcome; 2 studies 36 , 37 did not provide average intima-media thickness values; and participants’ selection did not match with age or sex in 2 studies. 38 , 39 One study 40 was further excluded because the reported FMD value was particularly high in both psoriatic patients and controls than other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Null CIMT extent findings have been found in Old Order Amish Americans , individuals living at extremes of the socioeconomic spectrum in Scotland , people with diabetes , individuals with SLE , and a Danish cohort of people with HIV infection . Positive vitamin D−CIMT associations have been reported in the contexts of diabetes , psoriasis , postmenopausal woman , secondary CVD prevention , and HIV infection .…”
Section: Discussionmentioning
confidence: 98%
“…Vitamin D‐VDR signalling in macrophages was proposed to limit the inflammatory response by targeting the miRNA‐155‐SOCS1 pathway, and by enhancing a negative feedback mechanism that atenuates TLR‐signalling. Vitamin D deficiency was reported in Ps patients …”
Section: Discussionmentioning
confidence: 99%